Epigallocatechin-3-Gallate Ameliorates Acute Lung Damage by Inhibiting Quorum-Sensing-Related Virulence Factors of Pseudomonas aeruginosa - Tang, Huaqiao; Hao, Suqi; Khan, Muhammad Faraz; Zhao, Ling; Shi, Fei; Li, Yinglun; Guo, Hongrui; Zou, Yuanfeng; Lv, Cheng; Luo, Jie; Zeng, Ze; Wu, Qiang; et al. (Frontiers in Microbiology, 2022)
The superbug Pseudomonas aeruginosa (P. aeruginosa) is among the most formidable antibiotic-resistant pathogens. With declining options for antibiotic-resistant infections, new medicines are of utmost importance to combat with P. aeruginosa. In our previous study, we demonstrated that Epigallocatechin-3-gallate (EGCG) can inhibit the production of quorum sensing (QS)-regulated virulence factors in vitro. Accordingly, the protective effect and molecular mechanisms of EGCG against P. aeruginosa-induced pneumonia were studied in a mouse model. The results indicated that EGCG significantly lessened histopathological changes and increased the survival rates of mice infected with P. aeruginosa. EGCG effectively alleviated lung injury by reducing the expression of virulence factors and bacterial burden. In addition, EGCG downregulated the production of pro-inflammatory cytokines, such as TNF-α, IL-1, IL-6, and IL-17, and increased the expression of anti-inflammatory cytokines IL-4 and IL-10. Thus, the experimental results supported for the first time that EGCG improved lung damage in P. aeruginosa infection by inhibiting the production of QS-related virulence factors in vivo.